Effectiveness and safety of aripiprazole oral solution in the acute treatment of schizophrenia in Chinese patients - Zhen Mao; Fang Dong; Anning Li; Feng Li; Junhong Zhu; Xiangdong Du; Gang Wu; Huaili Deng; Xueqin Yu; Jintong Liu; Shiping Xie; Xiaowei Tang; et al. (BMC Psychiatry)
Abstract Background This study investigates the effectiveness and safety of aripiprazole oral solution in Chinese patients with schizophrenia. Methods This was a multicenter, single-arm phase IV study involving 134 patients in China in the acute stage of schizophrenia from May 2021 to July 2022. The patients received aripiprazole oral solution 10 − 30 mg/d for 12 weeks. The effectiveness endpoints included the Positive and Negative Symptom Scale (PANSS) and the Clinical Global Impression (CGI) scale score. The safety endpoints included adverse events, laboratory inspection indicators (including the serum prolactin level [PRL]), and waist circumferences (WC). Results Ultimately, 86 patients (64.18%) completed the trial, and 21 patients (15.67%) dropped out due to poor effectiveness. From baseline to week eight, 43.28% of patients had a PANSS reduction of ≥ 50%, 82.84% of patients improved in the CGI-Improvement (CGI-I scale score of 1 − 3), and the percentage of patients with abnormal PRL and waist circumferences decreased significantly. In total, 45 patients (33.58%) experienced mild adverse drug reactions predominately manifested as extrapyramidal symptoms (EPSs; 9.70%), constipation (8.96%), and palpitations (7.46%). Upon further subgroup analysis, aripiprazole oral solution demonstrated significantly improved effectiveness in first-episode schizophrenia patients and those with symptoms of agitation. Conclusions Aripiprazole oral solution displayed positive clinical effectiveness and favorable tolerability in Chinese patients in the acute stage of schizophrenia. Clinical trial registration Clinical trial registration number: ChiCTR2100044653. Name of trial registration: A real-world study of Aripiprazole Oral Solution in the treatment of schizophrenia (Registration date: 25/03/2021). The full trial protocol can be accessed at the Chinese Clinical Trial Registry ( http://www.chictr.org.cn/ ).